Silver Powder의 입자 크기에 따른 Stretchable 전극 특성 연구 - 남현민; Hyun Min Nam; 백강준; Kang-jun Baeg; 남수용; Su Yong Nam (한국화상학회지, 2022)
본 연구에서는 실버 파우더의 입자 크기, 즉 평균 입자 크기가 2㎛과 7㎛, 이렇게 2가지 실버 페이스트를 개발하였다. 이렇게 개발된 실버 페이스트에 대해서 점도 및 점탄성, 경화후에 잔류용제 유무 확인을 위한 TGA측정, Strain에 따른 저항 변화 및 전극 표면 구조 변화에 대해서 검토하였다. 이러한 결과를 정리하면 Strain에 따른 저항 변화를 최소화하기 위해서는 실버 파우더의 입자를 2㎛정도인 것이 가장 바람직함을 알 수 있었다. In this study, two silver pastes were developed, with the particle size of silver powder, that is, the average particle size, 2㎛ and 7㎛. For the silver paste developed in this way, viscosity and viscoelasticity, TGA measurement to check the presence or absence of residual solvent after curing, resistance change according to strain, and electrode surface structure change were reviewed. Summarizing these results, it was found that it is most desirable to have a particle size of about 2㎛ in order to minimize the change in resistance due to strain.